2018
DOI: 10.1016/j.jacc.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Limb Events and Mortality in Patients With Peripheral Artery Disease

Abstract: Among individuals with lower extremity PAD, the development of MALE is associated with a poor prognosis, making prevention of this condition of utmost importance. The combination of rivaroxaban 2.5 mg twice daily and aspirin significantly lowered the incidence of MALE and the related complications, and this combination should be considered as an important therapy for patients with PAD. (Cardiovascular Outcomes for People Using Anticoagulation Strategies [COMPASS]; NCT01776424).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(272 citation statements)
references
References 19 publications
5
238
2
7
Order By: Relevance
“…These findings have important implications for clinicians managing patients with comorbid NVAF and T2D, in that anticoagulant choice may affect outcome risk beyond the traditional NVAF endpoints of stroke and systemic embolism. Patients who previously experienced MALE have a high risk of hospitalization, vascular amputations and death within 1 year of the event . These risks appear to be lower when receiving rivaroxaban compared with warfarin use, although mortality rates were not directly evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important implications for clinicians managing patients with comorbid NVAF and T2D, in that anticoagulant choice may affect outcome risk beyond the traditional NVAF endpoints of stroke and systemic embolism. Patients who previously experienced MALE have a high risk of hospitalization, vascular amputations and death within 1 year of the event . These risks appear to be lower when receiving rivaroxaban compared with warfarin use, although mortality rates were not directly evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a strong risk factor for the development and progression of PAD. 222,223 Several studies suggest that smoking cessation is associated with a lower rate of cardiovascular ischaemic and limb related vascular events, amputations, and death. 224,225 Therefore, patients who smoke should be advised to quit smoking at every follow up visit, and should be offered support from a smoking cessation team, if available.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…232 A small subgroup of patients within this study who had ALI also had a marked reduction in amputation and mortality rate. 223 Although the COMPASS trial was positive for patients with ALI, this was not the primary end point, and further research with a focus on ALI is needed.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Additional analysis of the PAD subgroup (stable PAD, CAD with asymptomatic PAD and stable carotid stenosis patients) in the Compass trial population [212,213] revealed, besides the 28 % general survival benefit, an [203].…”
Section: Anticoagulantsmentioning
confidence: 99%